2021
DOI: 10.2478/ats-2021-0013
|View full text |Cite
|
Sign up to set email alerts
|

Perceived effectiveness of adaptation strategies to climate change among rice farmers in Jigawa State, Nigeria: Implication for rice production

Abstract: This study assessed rice farmers’ perceived effectiveness of adaptation strategies to climate change in Jigawa State, Nigeria. Multi-stage sampling procedure was used to select 183 respondents from whom data were collected using questionnaires. Data were summarised using descriptive statistics, Chi-square, and Pearson Correlation. Majority of the respondents were males (98%), married (90%) and had formal education (66.1%) with a mean age of 41 years. On the overall, more than half (56.3%) of the respondents pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
4
0
1
Order By: Relevance
“…In terms of marital status of the respondents, majority (78.80%) were married and this agrees with Orifah et al (2021) that 90% of rice farmers were and few were single. This alludes to the facts that married farmers could be more productive and engaging in farming activities in order to provide food security for their households.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…In terms of marital status of the respondents, majority (78.80%) were married and this agrees with Orifah et al (2021) that 90% of rice farmers were and few were single. This alludes to the facts that married farmers could be more productive and engaging in farming activities in order to provide food security for their households.…”
Section: Resultssupporting
confidence: 85%
“…Table 2 shows that more than half (58.20%) of the respondents had informal education that can guide the mental attitude of the farmers for the awareness and acceptance of new rice value chain practices. This result is contrary to Orifah et al (2021) that 66.1% of the rice farmers had formal education. Also, (18.80%) never attended school, (13.60%) and (6.00) attained primary and secondary education, respectively.…”
Section: Resultscontrasting
confidence: 77%
See 2 more Smart Citations
“…The result implies that majority of the households in the study area have reasonable number of individuals who share household resources. Orifah et al (2020) also reported similar findings with respect to household size of smallholder rice farmers. Household dependency as estimated in this study was considered household members aged less than 15 and over 64 years old as dependent.…”
Section: Results and Discussion Socio-economic Characteristics Of Wet...supporting
confidence: 66%